2012
DOI: 10.1086/667617
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Leads to Counterproductive Intestinal Base Loss in the Gulf Toadfish (Opsanus beta)

Abstract: Oceanic CO(2) has increased from 280 to 380 μatm since preindustrial times and is expected to reach 1,900 μatm by 2300. In addition, regional upwelling zones exhibit levels up to 2,300 μatm, making exploration at future global projected CO(2) levels ecologically relevant today. Recent work has demonstrated that CO(2) exposure as low as 1,000 μatm induces acidosis in toadfish (Opansus beta), leading to metabolic compensation by retention of blood HCO(3) in an effort to defend pH. Since increased serosal HCO(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 57 publications
7
40
1
Order By: Relevance
“…Indeed, dietary trace element absorption occurs mainly in the intestine [30,31], and in marine fish (drinking water species), the intestine is also involved in acid-base balance and the ionoregulation (with gills and kidney [32,33]). Hereto, even if previous studies provided evidence of disturbances caused by p CO 2 on these processes in the fish intestine [34,35], our results indicated that it does not affect dietary essential element transfer in clownfish.…”
Section: Resultscontrasting
confidence: 83%
“…Indeed, dietary trace element absorption occurs mainly in the intestine [30,31], and in marine fish (drinking water species), the intestine is also involved in acid-base balance and the ionoregulation (with gills and kidney [32,33]). Hereto, even if previous studies provided evidence of disturbances caused by p CO 2 on these processes in the fish intestine [34,35], our results indicated that it does not affect dietary essential element transfer in clownfish.…”
Section: Resultscontrasting
confidence: 83%
“… Perry et al [2011] give XRD and Energy‐dispersion X‐Ray (EDX) of 11 different fish species in their supplemental material confirming that it is a high magnesium calcite with a maximum of 48.9 mol %. The magnesium content of the toadfish precipitates analyzed in the present study was found to be 47.9 mol % ± 0.7 (n = 8) [ Heuer et al , 2012]. Perry et al [2011, Figure 3] show that fish produced carbonates with ellipsoidal morphology, similar to the gulf toadfish, had a high Mg content of greater than 40 mol%.…”
Section: Resultsmentioning
confidence: 68%
“…After cleaning the precipitates were filtered through 0.45 μ m filter and dried. The magnesium and calcium content of the precipitates was determined after acid digestion by flame atomic adsorption spectrometry [ Heuer et al , 2012]. In brief, precipitates where sonicated using a rod sonicator in 10 ml deionized water, after which pH was lowered to 4.00 by addition of HCl under continuous gassing with N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to elevated sea surface temperature (SST), a growing body of literature has focused on the impacts ocean acidification will have on marine teleosts; however, the majority of these studies have focused primarily on tropical or temperate species (Melzner et al, 2009;Munday et al, 2009a;Munday et al, 2009b;Munday et al, 2010;Munday et al, 2011;Esbaugh et al, 2012;Heuer et al, 2012;Nowicki et al, 2012;Bignami et al, 2013;Chivers et al, 2014;Munday et al, 2014;Murray et al, 2014;Pope et al, 2014). Despite projections that indicate changes in SST and partial pressure of CO 2 (Ṗ CO2 ) in seawater will impact higher latitudes faster and to a greater Is warmer better?…”
Section: Introductionmentioning
confidence: 99%